Assessing police–community relationships: is there a gap in perceptions between police officers and residents? - Nalla, Mahesh (Policing and society, 2018)
The notion that community residents are key players responsible for the well-being of the larger society has become a cornerstone of approaches to modern policing in democratic societies. That is, residents partner with police to help maintain social order. An essential element of successful implementation of any programme is communication and understanding between various parties in the partnership. In this paper, we examine whether there is congruence between police officers and residents in how they perceive their relationships on various dimensions of police–community relations. These dimensions include residents’ respect for police and their willingness to cooperate in various community-policing activities. Using survey data collected in 2011 from a larger project with a national sample of 581 Slovenian police officers and 959 residents, we analyse both groups’ perceptions of community support of and willingness to partner with police officers. Results show that, on the one hand, residents appeared to have respect and confidence in police and were willing to cooperate with police officers in various crime prevention and community-policing activities. On the other hand, we find police officers’ perceptions of residents’ willingness to cooperate with the police ranked lower than residents’ reflections on these matters. On many of the dimensions of police–community partnerships, residents appeared more willing to cooperate and support the police compared to what officers perceived of residents’ willingness. This research identifies a gap in perceptions of citizen support of the police between Slovenian residents and police officers, which has to be bridged to make community policing more effective.